Strategic bidding and scheduling in reserve co-optimized based electricity spot markets - Francisco, Victor Joel E. (2008)
In electricity spot markets, revenue of independent power producers (IPPs) is dependent on successful bidding strategies. This research establishes a model for strategic bidding and short term generation scheduling in reserve co-optimized markets like the Philippine Wholesale Electricity Spot Market. The model, which is applicable to IPPs, is based on the combination of security constrained economic dispatch (SCED) and a probabilistic bidding model. The security constrained economic dispatch models fundamental price drivers in the market and takes into account transmission network parameters, marginal loss factors and reserve co-optimization to solve schedules and nodal prices for energy and reserve. The bidding model then determines optimum bid prices for each trading interval, by maximizing the probability of a bid being cleared while at the same time capitalizing on positive returns from the market. A simulation tool is developed to implement the strategic bidding model where strategies are derived for various scenarios. The test system includes an IPP with corresponding energy and reserve offers for electricity market trading. Several bidding strategies, derived from the model are then presented and discussed.